Children's behavioural problems and its associations with socioeconomic position and early parenting environment: findings from the UK Millennium Cohort Study. (13th August 2020) - Tamura, K.; Morrison, J.; Pikhart, H.
Abstract: Aims: To investigate behavioural problems throughout childhood and adolescent, and its relationship with socioeconomic position (SEP) and early parenting environment. Methods: Using data from the Millennium Cohort Study conducted in the UK, behavioural problems of 14 452 children were analysed using a growth curve model. The children were followed from birth to adolescence, and their behavioural problems were measured by the Strengths and Difficulties Questionnaire (SDQ). The SDQ was sub-scaled into externalising and internalising problems. After assessing the general trajectory of children's behavioural problems, variables representing SEP and parenting environments were introduced to the model to analyse the association with children's outcomes. Results: Overall, children's trajectories in externalising problems showed a decreasing trend while internalising problems increased as they aged. Household income and maternal education in early childhood were independently associated with children's behavioural problems, while the association for maternal occupation was significantly weaker. Positive early parenting environments attenuated the association between SEP and children's behavioural problems. Also, with regards to children's behavioural problems, positive parenting explained more variance between children compared to SEP. Favourable parent–child relationship buffered the income gradient in children's behavioural problems during early childhood, and although this buffering effect did not last until adolescence, those who had good parent–child relationships developed better outcomes regardless of their SEP. Conclusions: The results of the study emphasise the importance of a positive early parenting environment for improving and reducing the socioeconomic gap in children's behavioural problems and encourages policies to promote better parenting circumstances.